Remote sensing and GIS for analyzing and describing forest cover change in the ancestral domain of the Agta in General Nakar, Quezon - Martinez, Ma. Simeona Medina
The designation of national parks and forest lands by the government entails the regulation of some activities such as the allocation of space for certain uses. The Revised Forestry Code?s implementation in 1975 resulted in the designation of lands into Alienable and Disposable (A and D) and Forest Land categories. Agricultural activities or non-forest encroachment in the forest lands pose challenges to the policies that regulate the use of forest resources. When non-forest activities encroach into national parks and protected areas, they show the conflict between actual resource use and the policies that created these parks. This conflict between forest use and protection policies has implications on the utilization of forest resources and on the resource users themselves, such as the Agta indigenous inhabitants of Quezon Province.